2017
DOI: 10.6000/1927-520x.2017.06.01.4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Incidence of Uterine Torsion in Egyptian Buffaloes (Bubalus bubalis) and its Response for Rolling

Abstract: Objective: The present work was planned to study the incidence of uterine torsion in Egyptian buffaloes as well as its prognosis after mechanical treatment.Methods: A total number of 35 buffaloes of different ages, parities and stage of pregnancy with complain of colic and anorexia were included in the present study. These animals were examined rectally to detect stage of pregnancy, degree, direction, duration, location of uterine torsion. Mechanical handling of torsion cases and prognosis of recovered cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 6 publications
3
8
0
Order By: Relevance
“…This study revealed the incidence of the uterine torsion in buffaloes with regarding to parity, stage of pregnancy, age of dams, managing correction, and delivery type interference. Also, dam and fetal survival percentage was partially matched with Purohit and Gaur (2014) and Zaher et al (2017), who mentioned that right-side torsion mostly found at full term of pregnancy in pluriparous one.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This study revealed the incidence of the uterine torsion in buffaloes with regarding to parity, stage of pregnancy, age of dams, managing correction, and delivery type interference. Also, dam and fetal survival percentage was partially matched with Purohit and Gaur (2014) and Zaher et al (2017), who mentioned that right-side torsion mostly found at full term of pregnancy in pluriparous one.…”
Section: Discussionsupporting
confidence: 58%
“…Uterine torsion is more common in pluriparous animals and in late pregnancy (Zaher et al 2017). High fetal and maternal mortality rates have been reported in buffaloes suffered from the torsion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, among 50 buffaloes, 33 (66%) had suffered from 270-360° uterine torsion, 10 buffaloes (20%) with 180-270° uterine torsion and 7 buffaloes (14%) with 90-180° uterine torsion (Table 2). These observations were in accordance with the reports of Zaher et al (2017) and Nagaraju (2018). The probable reason for greater rotation of the pregnant uterus on its axis appears to be the instability of the uterus as the bubaline amnion fused at many places to the surrounding allantois, which is attached to the uterine wall and the gravid uterus rests on the abdominal floor during mid to late gestation with no stabilizing attachments; hence, rotatory fetal movements during the second stage of labor or late gestation would rotate the uterus.…”
Section: Results a N D Discussionsupporting
confidence: 94%
“…Among the 50 cases studied, the incidence of postcervical uterine torsion was more frequent (82%) when compared with the pre-cervical torsion (18%) ( Table 2). A similar observation was also made by the previous researcher in buffaloes (Purohit et al, 2013;Zaher et al, 2017). The higher incidence of postcervical uterine torsion may be attributed to the absence of the muscles in the cervical area of broad ligaments and lack of broad ligament support posterior to the cervix, which might leave the gravid uterus imbalanced and more prone to rotation (Prabhakar et al, 1997;Jeengar et al, 2015).…”
Section: Results a N D Discussionsupporting
confidence: 68%
“…Although severe tension could excite the vaginal stretch receptor, causing reflex abdominal straining, the high degree of torsion increased the likelihood of straining [ 22 ]. Because the majority of the time either the foetal limbs or the foetal membranes failed to reach the anterior vagina, there might be no straining [ 25 ].…”
Section: Introductionmentioning
confidence: 99%